Growth and nutritional status of pre-school children in India : rural-urban and gender differences - Bharati, Premananda (Array, 2009)
Abstract: This cross-sectional study of growth and nutritional status makes an attempt to find the gender and rural-urban differences among Indian preschool children. This study is based on the data of weight and height of children aged 0–35 months taken from 26 States (total 26,369 children; 13784 boys and 12585 girls). The children are found to be lighter and shorter compared to International standards irrespective of age and sex. Boys are heavier and taller than girls. Urban preschool children are heavier and taller compared to rural counterparts. In the urban area, higher percentages of girls are affected by underweight (37.1%) and stunting (35.0%) than boys. In rural areas, the prevalence of underweight is also higher among girls (47.9%) compared to boys (45.7%), which is found to be much significant (p< 0.01). There is a significant rural-urban as well as gender difference in growth and nutritional status of Indian preschool children